Sharing is Not Caring: Examining Intention of Sharing Misinformation Moderated by New Media Literacy - Wibowo, Damar Dhiyaan Hafidz; Wibowo, S. Kunto Adi (The Journal of Society and Media, 2024)
As the disruption era grows more and more apparent, so does the spread of misinformation. This research examines the intention to share misinformation moderated with New Media Literacy (NML). With data from 100 undergraduate students via online survey and analyzed using SmartPLS4, the study reveals that information-seeking significantly influences the intention to share misinformation, even when moderated by New Media Literacy. In contrast, status-seeking and entertainment demonstrate little impact on misinformation-sharing intent, also when moderated by New Media Literacy. Socializing, on the other hand, yields a significant but negative correlation with the intention to share misinformation, suggesting the need to share factually correct information firsthand. The finding suggests that cultivating clarity when sharing information on social media is crucial, especially when one’s intent is to seek information. This study contributes to the understanding of the factors influencing the spread of misinformation and highlights the importance of new media literacy in mitigating its effects